Health Impact and Cost-effectiveness of Volume, Tiered, and Sugar Content Sugar-sweetened Beverage Tax Policies in the US: A Micro-simulation Study (OR28-04-19). (13th June 2019) - Lee, Yujin; Mozaffarian, Dariush; Liu, Junxiu; Sy, Stephen; Abrahams-Gessel, Shafika; Wilde, Parke; Gaziano, Thomas; Micha, Renata
Abstract: Objectives: Sugar-sweetened beverage (SSB) intake is linked to weight gain, type 2 diabetes, and cardiovascular disease (CVD). SSBs taxes are a policy tool to reduce intake, and volume-based taxes have been passed in the US. Yet, the comparative health and economic impacts of volume-based, tiered, or sugar content-based SSB taxes have not been quantified. We aimed to estimate the health and economic impacts of these varying SSB tax designs in the US. Methods: A validated microsimulation model, CVD PREDICT, was used to estimate reductions in CVD events, diabetes cases, gains in quality-adjusted life-years (QALYs), costs, and cost-effectiveness of three SSB tax designs in US adults: (1) volume tax ($0.01/oz), (2) tiered tax (no tax for <5 g of added sugar/8 oz; $0.01/oz for 5–20 g/8 oz; and $0.02/oz for >20 g/8 oz, and (3) sugar content tax ($0.01/tsp of added sugar). Model inputs included national demographic and dietary data from NHANES 2009–2014; policy effects on consumer intakes, industry responses, and SSB-disease effects from meta-analyses; and policy costs (tax implementation, industry reformulation) and health-related costs (formal/informal healthcare costs, productivity costs) from established sources. Findings were evaluated over 10 years and a lifetime, with costs inflated to constant 2018 USD, and costs and QALYs discounted at 3% annually. Results: All SSB tax designs were cost-saving from all perspectives, compared to a base-case scenario accounting for voluntary industry reformulation (Table ). At 10 years, the volume tax would prevent 0.24 M CVD events, 0.11 M CVD deaths, and 0.03 M diabetes cases, gain 0.22 M QALYs, generate $35.18bn tax revenue, and save $14.45bn in formal healthcare costs. Corresponding values for the tiered tax were 0.46 M, 0.22 M, 0.06 M, 0.42 M, $54.99bn and $27.88bn; and for the sugar content tax, 0.37 M, 0.16 M, 0.05 M, 0.27 M, $19.97bn and $20.54bn. Projected benefits increased over a lifetime, and economic benefits were less from health and societal perspectives, excluding tax revenue. Conclusions: Implementing SSB taxes would generate substantial health gains and cost-savings for the US population. Taxing SSBs based on a tiered tax, followed by grams of sugar content, would be a more effective strategy than a volume tax to generate health and economic benefits. Funding Sources: NIH, NHLBI. Supporting Tables, Images and/or Graphs: